Dark Tourism - Meditating the historical and natural of Malaysian’s Al-Catraz Jerejak Island, Penang. - Md Zaki, Noor Fatin Izzati (2018)
This research more towards the kind of tourism that can be attracted and it can be in any of the tourism spot which inviting and allowed to exploring more kind of activities especially the historical part. The living museum is an approach that will be using as an inventive ways to provide awareness on historical area. It can evoke the emotion of the society to preserve and conserve the tangible and intangible elements that related with Malaysian history. The main focus is to preserve the historical value if the place where on the other side, provide an enjoyment and education awareness about the place. Somehow, society is able to learn and involved with this kind of activities. Hence, the aim and objectives of this study is to restore the historical and natural of Jerejak Island by create an appreciation towards the heritage value in order to promote awareness for public in Jerejak Island and objectives are to create an originality of the historical value of Jerejak Island by promoting a living museum for an education, To promote and highlight the historical significance of Jerejak Island to increase people awareness about the past event and to provide a master plan of Jerejak Island for dark tourism. The methodology that had been used for this study including the inventory and analysis of the site followed by attributes from 11 elements of NPS (National Park Service), site synthesis and treatment that will be using and the potential area of the stite study. Next, the overall processes of the design development with come out with landscape master plan of Jerejak Island. Instead, it will blend with the natural of the site study. The design guidelines of the site study not only preserve the historical building but also the rich of the flora, fauna and wildlife in the forest.